(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article explains the system will work with academic texts in the training of future humanitarian philologists on the basis of competence-based approach. Disclosed information aktivizatorskaya and motivational functions of academic teats; described forms of implementing the educational text.